Broad-spectrum ginsentides are principal bioactives in unraveling the cure-all effects of ginseng - Shining Loo; Antony Kam; Bamaprasad Dutta; Xiaohong Zhang; Nan Feng; Siu Kwan Sze; Chuan-Fa Liu; Xiaoliang Wang; James P. Tam (Elsevier, 2024)
Stress and illness connection is complex and involves multiple physiological systems. Panax ginsengs, reputed for their broad-spectrum "cure-all" effect, are widely prescribed to treat stress and related illnesses. However, the identity of ginseng's "cure-all" medicinal compounds that relieve stress remains unresolved. Here, we identify ginsentides as the principal bioactives that coordinate multiple systems to restore homeostasis in response to stress. Ginsentides are disulfide-rich, cell-penetrating and proteolytic-stable microproteins. Using affinity-enrichment mass spectrometry target identification together with in vitro, ex vivo and in vivo validations, we show that highly purified or synthetic ginsentides promote vasorelaxation by producing nitric oxide through endothelial cells via intracellular PI3K/Akt signaling pathway, alleviate α1-adrenergic receptor overactivity by reversing phenylephrine-induced constriction of aorta, decrease monocyte adhesion to endothelial cells via CD166/ESAM/CD40 and inhibit P2Y12 receptors to reduce platelet aggregation. Orally administered ginsentides were effective in animal models to reduce ADP-induced platelet aggregation, to prevent collagen and adrenaline-induced pulmonary thrombosis as well as anti-stress behavior of tail suspension and forced swimming tests in mice. Together, these results strongly suggest that ginsentides are the principal panacea compounds of ginsengs because of their ability to target multiple extra- and intra-cellular proteins to reverse stress-induced damages.